Pengaruh Media Sosial Terhadap Motivasi Belajar Siswa di Sekolah Dasar - Sandra Anggralita (Jurnal Primary (Kajian Ilmu Pendidikan Dasar dan Humaniora), 2022)
Social media is an interactive media technology that supports the sharing of information, interests, ideas and other forms of expression through virtual communities and networks. The birth of a technology has an impact on changes in the pattern of human life in society. . The development of technological advances, especially social media, also has an impact on students' learning motivation in elementary schools. This research is a quantitative research. The population in this study amounted to 24 fourth grade students at SDN Lemah Putro Sidoarjo. The sampling technique for this study used a random sampling technique, where the samples were taken as many as 24 students and data collection used a questionnaire. Data collection techniques used in this study were questionnaires and documentation. Data analysis techniques used were prerequisite normality tests and hypothesis testing. The results of this study indicate that social media has a significant effect on the learning motivation of elementary school students. This is evidenced by the results of the study showing the Kolgomorow-Smirnov Test values obtained from the results of calculating this normality test using SPSS version 24.0. from windows 10 it shows Asymp.sig. (2-tailed) of 0.200 greater than 0.05 or 0.200 > 0.05. Based on these data it can be stated that the data used in this study were normally distributed and passed the normality test using the One Sample Kolgomorov-Smirnov Test. The regression coefficient for the social media variable is 0.507, a positive sign, which means that the higher the influence of social media on the learning motivation of elementary school students. For the partial coefficient of using social media on student learning motivation, t2count (2.848) > ttable (2.082) and a significant value of 0.011 <0.05, then Ho1 is rejected and Ha1 is accepted. So testing the hypothesis shows that there is an effect of Social Media on the Learning Motivation of Class IV Elementary School Students